The age of reason - Sartre, Jean-Paul. (London Penguin Books, 2001)
The first novel of Sartre's monumental Roads to Freedom series, The Age of Reason is set in 1938 and tells of Mathieu, a French professor of philosophy who is obsessed with the idea of freedom. As the shadows of the Second World War draw closer -- even as his personal life is complicated by his mistress's pregnancy -- his search for a way to remain free becomes more and more intense.
Keywords: World War, 1939-1945--France--Fiction.